Introduction to international education : international schools and their communities - Hayden, Mary. (Thousand Oaks, Calif. : Sage Publications, 2006)
Examines the origins, definitions, and classifications of international education, discussing the benefits of international schools, the issues they face, and their role in the future of education.
Includes bibliographical references (p. [169]-185) and index.
Adult
Keywords: International education; International education